2017
DOI: 10.1073/pnas.1607350114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assembly of ultrasoft colloidal networks enables cell invasion within restrictive fibrillar polymers

Abstract: In regenerative medicine, natural protein-based polymers offer enhanced endogenous bioactivity and potential for seamless integration with tissue, yet form weak hydrogels that lack the physical robustness required for surgical manipulation, making them difficult to apply in practice. The use of higher concentrations of protein, exogenous cross-linkers, and blending synthetic polymers has all been applied to form more mechanically robust networks. Each relies on generating a smaller network mesh size, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…For example, since ULC microgels are more deformable than the regular crosslinked microgels 21 , they are particularly suitable for the development of nanomaterials for selective adsorption in physiological solution 20 , or as bio-sensors 52 , as recent findings show that the softness of microgels improves their adsorption onto a solid substrate 53 . Furthermore, it has been proven that ultra-low crosslinked microgels are a perfect system to generate porous fibrin networks facilitating cell migration and growth 54 . The capability of this system to have a topography under adsorption that depends on the compression and the suppression of crystallization in two dimensions would be of interest in these fields.…”
Section: Discussionmentioning
confidence: 99%
“…For example, since ULC microgels are more deformable than the regular crosslinked microgels 21 , they are particularly suitable for the development of nanomaterials for selective adsorption in physiological solution 20 , or as bio-sensors 52 , as recent findings show that the softness of microgels improves their adsorption onto a solid substrate 53 . Furthermore, it has been proven that ultra-low crosslinked microgels are a perfect system to generate porous fibrin networks facilitating cell migration and growth 54 . The capability of this system to have a topography under adsorption that depends on the compression and the suppression of crystallization in two dimensions would be of interest in these fields.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively our results support the fact that dense and mesh-like matrices prevent cell extension and migration 19,21,73 . Moreover, cells including ECs, require tracks either through aligned matrix and void space to migrate and form functional structures like tubes and lumen 74–76 . Our results show that ECs can form networks in stiffer matrices if the matrix is microstructure is loose but are likely inhibited from forming network in a soft matrix if the matrix is dense in microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, Douglas et al analyzed the formation of fibrin-μgel constructs made of fibrinogen and ULC pNiPAm microgels at higher concentrations, 8 mg/L and 4 mg/L, respectively. [25] At these concentrations the μ gels were found to form tubular-like networks of “pores” filled with μ gel particles throughout the fibrin clot. On the other hand, no significant differences in the fibrin structure of fibrin were observed within μ gel-free regions of the fibrin clot.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of these percolated colloidal networks were related to the fibrin polymerization kinetics rather to specific fiber– μ gel and μ gel– μ gel interactions. [25] The studies shown here were conducted at lower concentrations, i.e. about five times lower microgel concentration and at a fibrinogen concentration of 5 mg/mL.…”
Section: Resultsmentioning
confidence: 99%